Disentangling Radiative and Non-Radiative Deactivation Pathways in Cui -Based Tadf Emitters - Lemus-Chavez, L; Lemus-Chavez, L; Aravena-Ponce, D; Aravena-Ponce, D; Staforelli-Castillo, S; Staforelli-Castillo, S; Llanos-Silva, L; Llanos-Silva, L (John Wiley and Sons Inc, 2025)
The analysis of thermally activated delayed fluorescence emitters traditionally neglects the temperature dependence of the non-radiative singlet and triplet decay rates, which, for systems with quantum yields significantly departing from unity, unavoidably leads to inaccurate determination of the relevant photophysical parameters. Here we address this issue by performing a detailed photophysical study in three solid-state CuI complexes with the general formula [Cu(dmp)(PPh3)X] (X = Cl, Br, I). Decomposition of the measured temperature-dependent lifetimes τ(T) into their radiative and non-radiative contributions demonstrates a significant temperature dependence of the non-radiative rates, which leads to large deviations of the singlet-triplet gaps ΔEST from those determined in the traditional way. Our detailed analysis further confirms that non-radiative parameters follow the energy gap law and that zero field splitting effects, which are unrecognizable in the bare τ(T) data, are governed by the heavy atom effect. Our analysis is supported by measurements of the decay of the prompt fluorescence which is dominated by kISC in the studied compounds. © 2025 Wiley-VCH GmbH.